An investigation into robust spectral indices for leaf chlorophyll estimation - Main, Russell; Cho, Moses Azong; Mathieu, Renaud; OâKennedy, Martha M.; Ramoelo, Abel; Koch, Susan (ISPRS Journal of Photogrammetry and Remote Sensing, 2011)
Quantifying photosynthetic activity at the regional scale can provide important information to resource managers, planners and global ecosystem modelling efforts. With increasing availability of both hyperspectral and narrow band multispectral remote sensing data, new users are faced with a plethora of options when choosing an optical index to relate to their chosen or canopy parameter. The literature base regarding optical indices (particularly chlorophyll indices) is wide ranging and extensive, however it is without much consensus regarding robust indices. The wider spectral community could benefit from studies that apply a variety of published indices to differing sets of species data. The consistency and robustness of 73 published chlorophyll spectral indices have been assessed, using leaf level hyperspectral data collected from three crop species and a variety of savanna tree species. Linear regression between total leaf chlorophyll content and bootstrapping were used to determine the leafpredictive capabilities of the various indices. The indices were then ranked based on the prediction error (the average root mean square error (RMSE)) derived from the bootstrapping process involving 1000 iterative resampling with replacement. The results show two red-edge derivative based indices (red-edge position via linear extrapolation index and the modified red-edge inflection point index) as the most consistent and robust, and that the majority of the top performing indices (in spite of species variability) were simple ratio or normalised difference indices that are based on off-chlorophyll absorption centre wavebands (690â730 nm).
Keywords: Leaf level reflectance; Leaf chlorophyll; Red-edge; Vegetation indices; Photosynthetic activity

Steady-state chlorophyll a fluorescence detection from canopy derivative reflectance and double-peak red-edge effects - Zarco-Tejada, P. J.; Pushnik, J. C.; Dobrowski, S.; Ustin, S. L. (Remote Sensing of Environment, 2003)
A series of experiments carried out in a controlled environment facility to induce steady-state chlorophyll a fluorescence variation demonstrate that natural fluorescence emission is observable on the derivative reflectance spectra as a double-peak feature in the 690â710 nm spectral region. This work describes that the unexplained double-peak feature previously seen on canopy derivative reflectance is due entirely to chlorophyll fluorescence (CF) effects, demonstrating the importance of derivative methods for fluorescence detection in vegetation. Measurements were made in a controlled environmental chamber where temperature and humidity were varied through the time course of the experiments in both short- and long-term trials using Acer negundo ssp. californium canopies. Continuous canopy reflectance measurements were made with a spectrometer on healthy and stressed vegetation, along with leaf-level steady-state fluorescence measurements with the PAM-2000 Fluorometer during both temperatureâstress induction and recovery stages. In 9-h trials, temperatures were ramped from 10 to 35 Â°C and relative humidity adjusted from 92% to 42% during stress induction, returning gradually to initial conditions during the recovery stage. Canopy reflectance difference calculations and derivative analysis of reflectance spectra demonstrate that a double-peak feature created between 688, 697 and 710 nm on the derivative reflectance is a function of natural steady-state fluorescence emission, which gradually diminished with induction of maximum stress. Derivative reflectance indices based on this double-peak feature are demonstrated to track natural steady-state fluorescence emission as quantified by two indices, the double-peak index (DPi) and the area of the double peak (Adp). Results obtained employing these double-peak indices from canopy derivative reflectance suggest a potential for natural steady-state fluorescence detection with hyperspectral data. Short- and long-term stress effects on the observed double-peak derivative indices due to pigment degradation and canopy structure changes were studied, showing that both indices are capable of tracking steady-state fluorescence changes from canopy remote sensing reflectance.

The IndexDatabase - Henrich, V.; Krauss, G.; Götze, C.; Sandow, C. (2011)